Performing care New perspectives on socially engaged performance - Stuart Fish, Amanda; Thompson, James (Manchester University Press, 2020)
The book advances our understanding of performance as a mode of caring and explores the relationship between socially engaged performance and care. It creates a dialogue between theatre and performance, care ethics and other disciplinary areas such as youth and disability studies, nursing, criminal justice and social care. Challenging existing debates in this area by rethinking the caring encounter as a performed, embodied experience and interrogating the boundaries between care practice and performance, the book engages with a wide range of different care performances drawn from interdisciplinary and international settings. Drawing on interdisciplinary debates, the edited collection examines how the field of performance and the aesthetic and ethico-political structures that determine its relationship with the social might be challenged by an examination of inter-human care. It interrogates how performance might be understood as caring or uncaring, careless or careful, and correlatively how care can be conceptualised as artful, aesthetic, authentic or even 'fake' and 'staged'. Through a focus on care and performance, the contributors in the book consider how performance operates as a mode of caring for others and how dialogical debates between the theory and practice of care and performance making might foster a greater understanding of how the caring encounter is embodied and experienced.